Evaluation Of The Availability Of Job Enrichment equirements For Human Resources In Syrian Public Universities A Field Study For Administrative Workers At Tishreen University - Dayoub, Mohammad Abbas; Al- Rahman, Nisreen Abed; Al-Dali, Mohammad Ahed (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This study aimed to determine the availability of job enrichment requirements for administrative workers at Tishreen University, where the researcher distributed a questionnaire to a random sample of administrative workers amounting to / 351 / to collect data on the availability of the five requirements (skills, assignments, importance of tasks, independence, evaluation Performance), and the stability of the scale was measured using the Alpha Cronbach coefficient. The researcher analyzed the data using a set of tests, including descriptive statistics, and test differences for one sample, and a set of results was reached, the most important of which are: - Each of the skills required for workers, the employees ’sense of the importance of tasks, and the required identification of tasks needed to implement job enrichment at the university are available. - The required independence is not available, nor is the evaluation of the effective performance of tasks at Tishreen University necessary to apply job enrichment at the university. هدفت هذه الدراسة إلى تحديد مدى توفر متطلبات الإثراء الوظيفي للعاملين الإداريين في جامعة تشرين، حيث قام الباحث بتوزيع استبانة على عينة عشوائية من العاملين الإداريين بلغت /351/ مفردة لجمع بيانات حول توفر المتطلبات الخمسة (المهارات، تحديد المهام، أهمية المهام، الاستقلالية، تقييم الأداء)، وتم قياس ثبات المقياس بالاعتماد على معامل ألفا كرونباخ قام الباحث بتحليل البيانات باستخدام مجموعة من الاختبارات من بينها الإحصاءات الوصفية، واختبار الفروق لعينة واحدة باستخدام Spss 20، وتم التوصل إلى مجموعة من النتائج أهمها: - يتوفر كل من المهارات المطلوبة للعاملين، وشعور العاملين بأهمية المهام، والتحديد المطلوب للمهام اللازمة لتطبيق الإثراء الوظيفي في الجامعة. - لا تتوفر الاستقلالية المطلوبة، كما لا يتوفر تقييم الأداء الفعال للمهام في جامعة تشرين واللازمة لتطبيق الإثراء الوظيفي في الجامعة.